Chapter 11 Diagrams in Greek Medical Manuscripts - Bouras-Vallianatos, Petros (Dumbarton Oaks Research Library and Collection, 2022)
In this chapter I provide a critical examination of different forms of medical diagrams in Greek manuscripts, which are related to works by both ancient Greek and Byzantine medical authors. Due to the large number of surviving Greek medical codices and the fact that they have for the most part been little studied, my examination cannot be exhaustive. It focuses instead on representative examples, mostly derived from my personal consultation of medical manuscripts in various libraries.